Association of exercise with smoking-related symptomatology, smoking behavior and impulsivity in men and women. (1st November 2018) - Tosun, Nicole L.; Allen, Sharon S.; Eberly, Lynn E.; Yao, Meng; Stoops, William W.; Strickland, Justin C.; Harrison, Katherine A.; al'Absi, Mustafa; Carroll, Marilyn E.
Highlights: Women exercised less than men and had more negative affect, craving and withdrawal. Women smoked more cigarettes per day and had greater nicotine dependency. Positive affect was positively associated with exercise for both men and women. Negative affect and withdrawal were inversely associated with exercise for women. Impulsivity was inversely associated with exercise for both men and women. Abstract: Introduction: Despite extensive efforts to develop effective smoking cessation interventions, 70–85% of American cigarette smokers who quit relapse within one year. Exercise has shown promise as an intervention; however, many results have been equivocal. This study explored how exercise is associated with smoking-related symptomatology, smoking behavior and impulsivity in male and female smokers. Methods: Participants were recruited throughout the United States using the on-line crowdsourcing platform, Amazon's Mechanical Turk. They completed a survey with self-report measures assessing exercise, smoking-related symptomatology, smoking behavior and impulsivity. Differences between men and women were tested using t - and chi-square tests. Regression analyses tested for associations between exercise and smoking-related symptomatology, smoking behavior and impulsivity. Results: Participants (N = 604) were, on average, 32 (SD = 6.2) years old, mostly Caucasian, with at least some college education and approximately half were women. Women exercised slightly less than men and had more negative affect, craving, physical symptoms and withdrawal. Women smoked more cigarettes per day, had greater nicotine dependency and more years of smoking. Positive affect was positively associated with exercise for both men and women; however, this association was significantly stronger in women. Negative affect and withdrawal were inversely associated with exercise for women only. Impulsivity was inversely associated with exercise for both men and women. Conclusion: Exercise was significantly associated with several smoking-related symptomatology, smoking behavior and impulsivity variables for both men and women, suggesting that exercise may be a useful intervention for smoking cessation. Future prospective research should determine how exercise directly impacts smoking cessation.